The Holocene Paleoecology of Jenny Lake Area, Southwest Yukon, and Its Implications for Prehistory - Stuart, Glenn S.L.; Helmer, James W.; Hills, L.V. (ARCTIC, 1989)
The pollen stratigraphy of a core extracted from Jenny Lake, southwest Yukon, in 1984 has marked archaeological significance. Five palynological zones are identified as follows: Zone JL1, the oldest (ca. 12,500-9,500 B.P.), is a Betula shrub tundra assemblage; Zone JL2 (ca. 9,500-8,500 B.P.) an Alnus shrub tundra; Zone JL3 (ca. 8,500-4,500 B.P.) a Picea forest; Zone JL4 (ca. 4,500-2,000 B.P.) a Picea-Alnus woodland; and JL5 (ca. 2,000 B.P.-present) a Picea forest. The widely held belief that the Kluane-Aishihik area of the SW Yukon was covered by extensive grasslands well into the Holocene period is not supported by the palynology of the Jenny Lake Core. Instead, palynological evidence suggests that the area, which initially was a Betula shrub tundra, then Alnus shrub tundra, became a Picea-dominated forest by approximately 8,500 B.P. and remained forested to the present. The hypothesis stating early prehistoric hunters and gatherers in the SW Yukon were adapted to extensive Holocene grasslands until ca. 3,300-2,600 B.P. will have to be modified in view of these findings.Key words: Yukon, paleoecology, palynology, archaeology Mots clés: Yukon, paléoécologie, palynologie, archéologie